Methodological contributions towards the study of health care production: Lessons from a research study on barriers and access in mental health - Merhy, Emerson Elias; Feuerwerker, Laura Camargo Macruz; Silva, Erminia [UNESP] (My University, 2012)
This article presents methodological contributions and a conceptual innovation for thinking about the production of health care, stemming from a study on access and barriers in mental health carried out in the municipality of Campinas (São Paulo, Brazil). The study used a cartographic approach and, after an initial identification of the most complex cases (on the part of the teams of workers), adopted the users as guides to explore the different levels of production of their lives and to evaluate the possibility of forming a network of existential connections that produce life as a fundamental analyzer of access or barriers to care.
Contribuciones metodológicas para estudiar la producción del cuidado en salud: Aprendizajes a partir de una investigación sobre barreras y acceso en salud mental
Keywords: Cartography; Health services accessibility; Mental health